Solitary Keratoacanthoma at the Recipient Site of a Full-Thickness Skin Graft: A Case Report and Review of the Literature - Jeong Ho Kim; Sang-Hoon Lee; Seung-Phil Hong; Jiye Kim; Sug Won Kim (Archives of Plastic Surgery, 2023)
A 57-year-old man presented with a pigmented papule, 0.4 cm in diameter, on the left lower eyelid. Skin biopsy revealed a basal cell carcinoma, which was excised through a wide excision followed by a full-thickness skin graft (FTSG). Two weeks after the surgery, an erythematous nodule developed in the lower margin of the graft recipient site. The nodule size increased rapidly over 2 weeks, becoming dome-shaped with a central hyperkeratotic plug. A diagnosis of keratoacanthoma (KA) was made, and surgical excision was performed. Histological findings revealed a large, well-differentiated squamous tumor with a central keratin-filled crater and buttress. The human papilloma virus (HPV) genotyping results were negative. Risk factors for KA include trauma, old age, exposure to ultraviolet (UV) radiation, immunosuppression, and HPV infection. KA has most often been reported to develop at the donor site. Although the pathogenesis of KA is unclear, trauma is believed to act as a second insult to a preceding oncogenic insult, such as exposure to UV radiation, resulting in a koebnerization. Herein, we report a case of solitary KA at a FTSG recipient site. This report presents information that may provide guidance during dermatologic surgeries.